Relationship between motor learning and gambling propensity in Parkinson's disease. Issue 1 (2nd January 2022) - Ueda, Naohisa; Higashiyama, Yuichi; Saito, Asami; Kimura, Katsuo; Nakae, Yoshiharu; Endo, Masanao; Joki, Hideto; Kugimoto, Chiharu; Kishida, Hitaru; Doi, Hiroshi; Takeuchi, Hideyuki; Koyano, Shigeru; et al.
ABSTRACT: Introduction: The basal ganglia and related dopaminergic cortical areas are important neural systems underlying motor learning and are also implicated in impulse control disorders (ICDs). Motor learning impairments and ICDs are frequently observed in Parkinson's disease (PD). Nevertheless, the relationship between motor learning ability and ICDs has not been elucidated. Methods: We examined the relationship between motor learning ability and gambling propensity, a possible symptom for prodromal ICDs, in PD patients. Fifty-nine PD patients without clinical ICDs and 43 normal controls (NC) were administered a visuomotor rotation perturbation task and the Iowa Gambling Task (IGT) to evaluate motor learning ability and gambling propensity, respectively. Participants also performed additional cognitive assessments and underwent brain perfusion SPECT imaging. Results: Better motor learning ability was significantly correlated with lower IGT scores, i.e., higher gambling propensity, in PD patients but not in NC. The higher scores on assessments reflecting prefrontal lobe function and well-preserved blood perfusion in prefrontal areas were correlated with lower IGT scores along with better motor learning ability. Conclusions: Our findings suggest that better motor learning ability and higher gambling propensity are based on better prefrontal functions, which are in accordance with the theory that the prefrontal cortex is one of the common essential regions for both motor learning and ICDs.